Manufacturing method of rare earth sintered magnet
By adjusting the water ratio in the oil agent used in the recovery of rare earth sintered magnet powders to 0.005% or less, the method effectively controls oxygen concentration and prevents moisture absorption, addressing the challenge of irregular magnet properties due to grain boundary thickness variations.
Patent Information
- Application Number
- JP2023164459
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing methods for manufacturing rare earth sintered magnets face challenges in controlling the thickness of two-particle grain boundaries, leading to irregular magnet properties due to variations in oxygen concentration, which is difficult to manage especially when moisture from the atmosphere is absorbed during the manufacturing process.
A method involving the grinding of rare earth raw material alloys into powders, followed by recovery in a container supplied with an oil agent, where the water ratio in the oil agent is adjusted to 0.005% or less, effectively preventing moisture absorption and controlling oxygen concentration.
This approach successfully suppresses moisture absorption and oxidation during the manufacturing process, allowing for precise control of the grain boundary phase and achieving improved magnet properties with modified two-particle grain boundaries.
Smart Images

Figure 2025055177000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a rare earth sintered magnet. [Background technology]
[0002] RTB sintered magnets (R is a rare earth element that must contain at least one of Nd and Pr. T is Fe and Co, with over 90% of T being Fe by mass. B is boron) are a representative example of rare earth sintered magnets, and are known as the most high-performance permanent magnets, and are used in a variety of motors, including those for electric vehicles (EV, HV, PHV, etc.), industrial equipment, and home appliances. RTB sintered magnets are mainly R2T 14 It is composed of a main phase made of B compounds and a grain boundary phase (hereinafter sometimes simply referred to as "grain boundary") located at the grain boundary portion of this main phase. 14 The B compound is a ferromagnetic phase with high magnetization.
[0003] RTB sintered magnets have a coercive force H cJ (Hereinafter, simply "coercive force" or "H cJ This causes a problem of irreversible thermal demagnetization, as the magnetization temperature drops and the magnetization rate drops. For this reason, RTB sintered magnets, which are used in electric vehicle motors in particular, have a high H cJ It is required that the applicant have:
[0004] In RTB sintered magnets, R2T 14 When a part of the light rare earth elements (mainly Nd and / or Pr) contained in R in the B compound is replaced with heavy rare earth elements (mainly Dy and / or Tb), H cJ It is known that the H cJ will improve.
[0005] However, R2T 14 When the light rare earth elements in the B compound are replaced with heavy rare earth elements, the H of the RTB sintered magnet cJ While the residual magnetic flux density B r(Hereinafter, simply "B r In addition, heavy rare earth elements, especially Dy, are scarce and have limited production areas, so their supply is unstable and their prices fluctuate greatly. For this reason, in recent years, users have been promoting the use of H as little as possible without using heavy rare earth elements. cJ There is a need to improve this.
[0006] Patent Document 1 discloses an RTB rare earth sintered magnet with increased coercivity while reducing the Dy content. The composition of this sintered magnet is limited to a specific range in which the amount of B (boron composition ratio or boron concentration) is relatively low compared to commonly used RTB alloys, and contains one or more metal elements selected from Al, Ga, and Cu. As a result, R2T occurs at the grain boundaries. 17 Phase is generated and this R2T 17 Transition metal-rich phase (R6T 13 As the volume ratio of H cJ will improve. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2013 / 008756 Summary of the Invention [Problem to be solved by the invention]
[0008] High B while reducing the content of heavy rare earth elements r and high H cJ In order to realize a rare earth sintered magnet with this property, a technology is being investigated in which the thickness of the two-particle grain boundary is controlled by relatively reducing the amount of B.
[0009] On the other hand, it was found that even if the amount of rare earth elements and B in the raw alloy are adjusted to the desired range, the thickness of the two-particle grain boundary may not be sufficiently controlled depending on the manufacturing process, resulting in deterioration of the magnetic properties. This is thought to be because the grain boundary phase changes depending on the amount of oxygen in the rare earth sintered magnet. However, it was found that even if each process in the manufacturing stage (from the crushing process to the sintering process) is managed in a low-oxygen atmosphere, it is difficult to control the variation in oxygen concentration in the final rare earth sintered magnet to 400 ppm or less. It was also found that the cause of this is moisture that is absorbed into the raw alloy powder of the rare earth sintered magnet from the atmosphere during the manufacturing process.
[0010] The method for producing a rare earth sintered magnet according to the present disclosure can prevent moisture from being absorbed into the raw alloy powder of the rare earth sintered magnet from the atmosphere during the production process. [Means for solving the problem]
[0011] The method for producing a rare earth sintered magnet of the present disclosure includes the steps of pulverizing a rare earth raw alloy to produce powder of the rare earth raw alloy, recovering the powder using a collection container, supplying an oil to the collection container before, after or during the recovery of the powder, and adjusting the moisture ratio, which is the ratio of the mass of moisture in the oil to the mass of the powder to be recovered, in the oil supplied to the collection container to 0.005% or less. Effect of the Invention
[0012] According to the embodiment of the present disclosure, it is possible to prevent moisture from being absorbed into the raw alloy powder of the rare earth sintered magnet from the atmosphere during the manufacturing process. More specifically, the finely pulverized powder, which is in an active state where it is most susceptible to oxidation immediately after being produced by a pulverizer, is placed in an oil with an adjusted moisture content, thereby preventing oxidation caused by moisture. As a result, it is possible to realize a rare earth sintered magnet with a modified two-particle grain boundary. [Brief description of the drawings]
[0013] [Figure 1A]FIG. 2 is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet. [Figure 1B] FIG. 1B is a further enlarged schematic diagram of the dashed rectangular area in FIG. 1A. [Diagram 2] 1 is a flowchart outlining a method for producing a rare earth sintered magnet according to an embodiment of the present disclosure. [Diagram 3] FIG. 1 is a diagram illustrating a configuration example of a grinding system according to an embodiment of the present invention. [Figure 4] 5 is another flowchart showing an outline of the method for producing a rare earth sintered magnet according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present disclosure will be described using an RTB sintered magnet as an example of a rare earth sintered magnet.
[0015] Conventionally, in an RTB sintered magnet, for example, when (1) the content of R (at least one of rare earth elements, which necessarily contains at least one of Nd and Pr) is 27 mass% or more and 34 mass% or less of the entire RTB sintered magnet, (2) T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, T necessarily contains Fe, and the content of Fe in the entire T is 80 mass% or more, and (3) the molar ratio of T to B ([T] / [B]) is more than 14.0 and 15.0 or less, an element such as Ga is added to thicken the two-particle grain boundary and increase the H cJ It is known that it is possible to improve
[0016] The molar ratio of T to B ([T] / [B]) is the ratio (a / b) of the number of moles (a) obtained by dividing the analytical value (mass%) of the concentration of each element (Fe and at least one of Co, Al, Mn, and Si) constituting T by the atomic weight of each element, to the number of moles (b) obtained by dividing the analytical value (mass%) of the concentration of B by the atomic weight of B.
[0017] When the molar ratio of T to B ([T] / [B]) exceeds 14.0, the B content is R2T 14 This means that the ratio of the main phase (R2T 14 The amount of B is reduced relative to the amount of T used to form the compound (B).
[0018] Next, the basic structure of an RTB based sintered magnet will be described.
[0019] RTB sintered magnets have a structure in which powder particles of raw alloys are bonded together by sintering, and are mainly 14 It is composed of a main phase made of B compounds and a grain boundary phase located at the grain boundaries of this main phase.
[0020] FIG. 1A is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet, and FIG. 1B is a schematic diagram further enlarging the dashed rectangular area in FIG. 1A. In FIG. 1A, an arrow of 5 μm in length is shown as an example for reference, showing the reference length of the size. As shown in FIG. 1A and FIG. 1B, an RTB based sintered magnet is mainly composed of R2T 14 The grain boundary phase 14 is composed of a main phase 12 made of a B compound and a grain boundary phase 14 located at the grain boundary portion of the main phase 12. As shown in FIG. 1B, the grain boundary phase 14 is composed of two R2T 14 B compound grains are adjacent to each other in the two-particle grain boundary phase 14a, and there are three or more R2T 14 The B compound grains include adjacent grain boundary triple junctions 14b.
[0021] R2T, which is main phase 12 14 The B compound is a ferromagnetic phase with high saturation magnetization and anisotropic magnetic field. Therefore, in RTB sintered magnets, the R2T 14 By increasing the proportion of B compounds, r It can improve R2T 14 In order to increase the ratio of B compounds, the amounts of R, T, and B in the raw alloy should be adjusted to R2T 14 The best way is to get the stoichiometric ratio of B compound (R amount:T amount:B amount = 2:14:1).14 When the amount of B or R for forming the B compound is less than the stoichiometric ratio, the grain boundary phase 14 generally contains an Fe phase or an R2T phase. 17 Soft magnetic phases such as H cJ However, the amount of B is reduced by R2T 14 When the amount of B compound is less than the stoichiometric ratio and one or more metal elements M selected from Al, Ga, and Cu are contained, R2T 17 The grain boundaries become thicker due to the formation of transition metal-rich phases (e.g., RT-Ga phases) at the grain boundaries from the phase, resulting in high H cJ can be obtained.
[0022] In RTB sintered magnets, in order to thicken the two-particle grain boundary, it is important to control not only the amount of B but also the amount of oxygen. According to the study by the present inventors, in order to precisely control the amount of oxygen contained in the RTB sintered magnet material within a predetermined range during the manufacturing process of the powder compact obtained by pulverizing the raw magnet alloy, it is important to suppress oxidation caused by moisture by placing the finely pulverized powder in an active state where it is most likely to oxidize immediately after being produced by the pulverizer in an oil solution with an adjusted moisture content. In the embodiment of the present disclosure, it was found that it is possible to more effectively suppress oxidation of the powder by managing and controlling the moisture content of the oil solution according to the mass of the powder in the oil solution, rather than simply reducing the moisture content of the oil solution.
[0023] <Embodiment> Next, an outline of the method for producing a rare earth sintered magnet of this embodiment will be described with reference to Fig. 2. As shown in Fig. 2, the method for producing a rare earth sintered magnet of this embodiment includes the steps of: pulverizing a rare earth raw alloy to produce powder of the rare earth raw alloy (S10), recovering the powder using a recovery container (S12), supplying an oil agent to the recovery container through a pipe filled with an inert gas before, after or during the recovery of the powder (S14), and adjusting the moisture ratio, which is the ratio of the mass of moisture in the oil agent to the mass of the powder to be recovered, in the oil agent supplied to the recovery container to 0.005% or less.
[0024] The important point of the manufacturing method in this embodiment is to adjust the moisture ratio, which is the ratio of the moisture mass in the oil to the mass of the powder to be collected, in the oil solution supplied to the collection container to 0.005% or less. The technical effect of this will be described later.
[0025] Each of the above steps will now be described.
[0026] <Step of Producing Rare Earth Alloy Powder (S10)> In this embodiment, a step S10 is carried out to prepare rare earth alloy powder using a jet mill pulverizer as a step (fine pulverization step) of pulverizing the raw alloy to obtain rare earth alloy powder. Prior to step S10, a hydrogen pulverization step is preferably carried out to prepare coarsely pulverized rare earth alloy powder. Here, the composition of the rare earth alloy raw alloy is as follows. R: 26.5 to 33.5 mass% (R is a rare earth element and must contain at least one of Nd and Pr), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85~0.92% by mass, T: 61.5 mass% or more (T is Fe and Co, and 90% or more of T is Fe by mass ratio), Tb: 0.30% by mass or less, and Dy: 0.30% by mass or less
[0027] By adjusting the amount of B to the above range, R6T is formed at the grain boundaries of rare earth sintered magnets. 13 Ga is formed and the two-grain boundary becomes thicker, for example, B of 1.39T or more. r and high H exceeding 1640kA / m cJ In order to reliably thicken the two-particle grain boundary, it is more preferable that the molar ratio of T ([T] / [B]) is more than 14.0 and 15.0 or less.
[0028] The rare earth-based raw alloy having the above composition can be produced, for example, by a strip casting method. The rare earth-based alloy may contain a plurality of alloy components having different compositions. By having the above composition as a whole, the above-mentioned two-particle grain boundary is thickened to obtain a high H cJ It is possible to obtain the effect of realizing the above.
[0029] The hydrogen pulverization process may include a hydrogen absorption process in which hydrogen is absorbed into the rare earth alloy at a temperature of 200°C or less in a treatment chamber, and a dehydrogenation process in which hydrogen is exhausted from inside the treatment chamber and the rare earth alloy is heated to a temperature in the range of, for example, 80°C or more and 650°C or less to perform a dehydrogenation process and produce a coarsely pulverized powder.
[0030] The average particle size of the coarsely pulverized powder is, for example, 10 μm or more and 500 μm or less. The average particle size (d50) in this disclosure can be measured by an airflow dispersion type laser diffraction method (based on JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size means the particle size (median diameter: d50) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.
[0031] In the fine pulverization step (S10), the coarsely pulverized powder is pulverized to obtain a fine powder having a median diameter d50 of, for example, 3.5 μm or less. The fine pulverization step may include a step of mixing an organic grinding aid with the coarsely pulverized powder. An example of the organic grinding aid is zinc stearate. The average particle size d50 of the finely pulverized powder is preferably 2.0 μm or more and 3.5 μm or less.
[0032] Next, an example of a grinding system including a jet mill grinding device and a collection container will be described with reference to Fig. 3. Fig. 3 is a diagram showing a schematic configuration example of a grinding system 1000 in this embodiment. In this example, the grinding system 1000 includes a jet mill grinding device 100, a cyclone collecting device 200, a bag filter device 300, a collection container 400, and an oil agent supplying device 500.
[0033] The jet mill pulverizer 100 receives a supply of materials to be pulverized from a raw material tank (not shown) via a raw material input pipe 34. A plurality of valves are provided in the raw material input pipe 21, and the internal pressure of the jet mill pulverizer 100 is appropriately maintained by opening and closing the valves. The materials to be pulverized introduced into the jet mill pulverizer 100 are finely pulverized by collisions between the materials to be pulverized due to high-speed jets of inert gas from the nozzle pipe 31 and collisions with collision plates installed to efficiently advance pulverization.
[0034] Powder of rare earth alloys such as alloys for RTB sintered magnets is active and easily oxidized. For this reason, the gas used in the jet mill pulverizer 100 is generally a dry (high purity) inert gas such as nitrogen, argon, or helium with a dew point of -60°C dp or lower in order to avoid the risk of heat generation and fire and to reduce the oxygen content as an impurity to improve the performance of the magnet.
[0035] The powder particles (finely pulverized powder) finely pulverized inside the jet mill pulverizer 100 are carried by the ascending air current and guided from the upper outlet to the inlet pipe 22 of the cyclone collector 200. Coarse particles that are not sufficiently pulverized may be separated, for example, by a classifying rotor installed to classify coarse particles larger than the median diameter (d50), remain inside the jet mill pulverizer 100, and may be subjected to a further crushing process by collision. Such classification of coarse particles may be performed using centrifugation by a swirling flow instead of using a classifying rotor. In this way, the coarsely pulverized powder fed into the jet mill pulverizer 100 is pulverized into finely pulverized powder having a particle size distribution with an average particle size (median diameter: d50) of, for example, 2.0 μm to 4.5 μm, and then moved to the cyclone collector 200.
[0036] The cyclone collector 200 is used to separate the powder from the airflow carrying the powder. Specifically, coarsely pulverized powder of an alloy for RTB-based sintered magnets is pulverized in a jet mill at a front stage, and the finely pulverized powder produced by the pulverization is supplied to the cyclone collector 200 through an inlet pipe 22 together with the gas used for the pulverization. A mixture of an inert gas (pulverization gas) and the pulverized finely pulverized powder forms a high-speed airflow and is sent to the cyclone collector 200. The cyclone collector 200 is used to separate the pulverized gas from the finely pulverized powder. The finely pulverized powder separated from the pulverized gas is collected in a collection container (collection device) 400 through a pipe 24 connected to an exhaust port 40. The pulverized gas is supplied to a bag filter device 300 through an outlet pipe 23 of the cyclone collector 200. The bag filter device 300 collects very small particles, and clean gas is discharged to the outside through an exhaust port 25. Although it is possible to use a bag filter for such solid-gas separation without using the cyclone collector 200, this would have a large impact on the environment and safety, such as the dispersion of finely pulverized powder into the air due to damage to the filter. For this reason, it is desirable to further separate fine particles from the gas separated by the cyclone collector 200 by using a bag filter, as shown in the example of Fig. 3.
[0037] The dew point in the grinding chamber and the amount of coarsely ground powder supplied to the jet mill grinding device depend on the grinding time and the size of the jet mill grinding device, but in a preferred embodiment, the inert gas can be adjusted so that the dew point during grinding is -55°C dp or more and -30°C dp or less. Examples of inert gases are nitrogen, argon, and helium. Among them, nitrogen is the most preferred because high purity gas is available at low cost. Therefore, in a preferred embodiment, the inert gas is nitrogen gas.
[0038] In the grinding system 1000 shown in FIG. 3, a piping 24 for transferring the finely pulverized powder produced by the jet mill grinding apparatus 100 to a collection container 400 is provided in the cyclone collector 200. When the cyclone collector 200 is not provided, such a piping 24 may be provided directly in the jet mill grinding apparatus 100. In the example of FIG. 3, a gas introduction pipe 32 communicating with the inside of the piping 24 is provided. The gas introduction pipe 32 may be provided in the upper part of the collection container 400. By supplying an inert gas from an inert gas supply unit 42 to the gas introduction pipe 32, the inside of the piping 24 and the inside of the collection container 400 can be filled with the inert gas.
[0039] <Step (S12) of recovering powder using a recovery container> By using the grinding system 1000 having the above-mentioned configuration, it becomes possible to move the finely pulverized powder produced by the jet mill grinding device 100 through the piping 24 filled with an inert gas to the collection container 400 filled with an inert gas.
[0040] In this embodiment, a dry gas (e.g., dry nitrogen gas) with a dew point of -80°Cdp or more and -30°Cdp or less may be used as the inert gas supplied to the gas introduction pipe 32. Since the finely pulverized powder is moved to the collection container 400 while the pipe 24 and the collection container 400 are filled with such an inert gas, it is possible to collect the finely pulverized powder without contacting water vapor in the atmosphere. In this way, the oxygen concentration in the powder of the rare earth alloy during the manufacturing process can be precisely controlled within a predetermined range without being increased by water vapor, and as a result, it is possible to more reliably adjust the grain boundary phase of the finally obtained rare earth sintered magnet to an appropriate range and achieve the desired two-particle grain boundary thickness.
[0041] The gas introduction pipe 32 in this embodiment is preferably made of a flexible non-metallic material. If the gas introduction pipe 32 is made of a material with high rigidity such as a metal material, the presence of the gas introduction pipe 32 makes it difficult to take out the powder (finely pulverized powder) that has moved to the collection container 400 or to perform maintenance of the pulverization system 1000. The gas introduction pipe 32 is preferably made of fluororesin. Since fluororesin has a low water vapor permeability, it is possible to prevent water vapor in the atmosphere from passing through the gas introduction pipe 32 and entering the inside of the above-mentioned pipe 24 and collection container 400. As a result, the dew point inside the pipe 24 and collection container 400 can be maintained at -30°C dp or less.
[0042] According to the study by the present inventor, when an inert gas is supplied to the inside of the pipe 24 and the collection container 400 using a gas introduction pipe made of, for example, polyurethane, it was found that water vapor in the atmosphere may pass through the gas introduction pipe and oxidize the powder collected in the collection container 400. Therefore, even if the dew point of the inert gas inside the inert gas supply unit 42 is adjusted to be −80° C. dp or higher and −30° C. dp or lower, the dew point inside the pipe 24 and the collection container 400 may not be maintained to be −80° C. dp or higher and −30° C. dp or lower. According to this embodiment, since the gas introduction pipe 32 is made of a fluororesin that is difficult for water vapor to pass through, the dew point inside the pipe and the collection container can be maintained to be −80° C. dp or higher and −30° C. dp or lower when the inert gas is supplied through the gas introduction pipe 32. Therefore, according to the grinding system 1000 of Figure 3, the process of transferring finely pulverized powder from the jet mill grinding apparatus 100 to the collection container 400 through the piping 24 can be carried out while maintaining the dew point inside the piping 24 and the collection container 400 at a value between -80°Cdp and -30°Cdp.
[0043] <Step of Supplying Oil to Collection Container (S14)> The grinding system 1000 in this embodiment further includes an oil agent supplying device 500 that supplies an oil agent to the collection container 400. The oil agent supplying device 500 is connected to the collection container 400 by a pipe .
[0044] The timing for supplying the oil agent to the collection container 400 may be before or after collecting the powder, or during collection. The oil agent may be stored in the inside of the collection container 400 before the powder is transferred to the collection container 400 via the pipe 24. In this case, the supplied powder sinks in the oil agent stored in the collection container 400. Since the powder in the oil agent is prevented from coming into contact with the atmospheric gas, direct oxidation by oxygen or water vapor in the air can be suppressed.
[0045] However, according to the study by the present inventor, it was found that as the storage time of the powder in the oil increases, the powder is oxidized by the moisture in the oil, and the oxygen concentration of the powder increases. For this reason, in the embodiment of the present disclosure, the oxidation of the powder is suppressed by controlling the moisture content of the oil. Specifically, for example, the moisture content can be adjusted by passing an inert gas through the oil stored in the collection container 400 to reduce the moisture mass in the oil. Note that since the powder inside the collection container 400 is in an oil whose moisture concentration is controlled within a predetermined range, even if the powder is kept in the collection container 400 for a long time (for example, 60 minutes or more), the oxidation of the powder is suppressed, and the increase in the amount of oxygen (oxygen concentration) in the final rare earth sintered magnet can be suppressed. The collection container 400 may be configured to be detachable from the grinding system 1000.
[0046] In the embodiment, the moisture content in the oil is not simply reduced, but the moisture ratio, which is the ratio of the "mass of moisture in the oil" to the "mass of powder in the oil (powder to be recovered)", is adjusted to 0.005% or less. This is because the oxidation of the powder in the oil does not depend only on the moisture mass in the oil, but also on the mass of the powder present in the oil (recovered powder mass). If the moisture ratio exceeds 0.005%, the powder that is shielded from the atmosphere by the oil is oxidized by the moisture dissolved in the oil. The oxidation progresses with the increase in the time that the powder is in the oil. According to the embodiment, even if the powder is kept in the oil for a long time (for example, one hour or more), the increase in the oxygen content of the final rare earth sintered magnet can be suppressed. Preferably, the moisture ratio is 0.003% or less. The moisture ratio can be measured using a known moisture-in-oil meter, for example, a moisture-in-oil meter TEKHNEPort-Oil manufactured by TEKHNE Measurement Co., Ltd.
[0047] <Step of adjusting the water ratio of the oil agent (S16)> The moisture content of the oil agent can be adjusted by passing an inert gas through the oil agent stored in the tank of the oil agent supplying device 500 to reduce the moisture mass in the oil agent. In this embodiment, the "moisture ratio", which is the ratio of the moisture mass in the oil agent to the mass of the powder transferred from the jet mill crushing device 100 to the collection container 400, is adjusted to 0.005% or less. According to the crushing system 1000 having the above configuration, the above steps S12, S14, and S16 can be executed.
[0048] 4. The method for producing a rare earth sintered magnet in this embodiment includes a step (S18) of producing a powder compact from the powder (finely pulverized powder) collected in the collection container 400 by the above-mentioned method, and a step (S20) of sintering the powder compact to produce a rare earth sintered magnet material. Preferably, the method further includes a step (S22) of preparing a diffusion source powder made of an RMA alloy, and a step (S24) of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material, thereby diffusing elements contained in the diffusion source powder into the inside of the rare earth sintered magnet material.
[0049] Examples of each of the above steps will now be described.
[0050] <Step of producing powder compact (S18)> The powder compact can be produced from the powder (finely pulverized powder) by, for example, pressing in a magnetic field. When pressing in a magnetic field, it is preferable to form the powder compact by pressing in an inert gas atmosphere or wet pressing from the viewpoint of suppressing oxidation. In particular, in wet pressing, the surfaces of the particles constituting the powder compact are covered with a dispersant such as an oil agent, suppressing contact with oxygen or water vapor in the air. This makes it possible to prevent or suppress oxidation of the particles by the air before, during, or after the pressing process.
[0051] When wet pressing in a magnetic field is performed, a slurry is prepared by mixing a finely pulverized powder with a dispersion medium, and the slurry is supplied to a cavity in a mold of a wet pressing apparatus and press-molded in a magnetic field. The dispersion medium is a liquid in which a slurry can be obtained by dispersing an alloy powder therein. A preferred dispersion medium used in the present disclosure can be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increase in viscosity may strengthen the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet pressing in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. Furthermore, if the fractional point of the mineral oil or synthetic oil exceeds 400°C, it becomes difficult to remove oil after obtaining a compact, and the amount of residual carbon in the sintered body may increase, resulting in a decrease in magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. Vegetable oil may also be used as the dispersion medium. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.
[0052] The obtained alloy powder is mixed with a dispersion medium to obtain a slurry. The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. 3This is because, at a flow rate of 1000 / sec, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less by mass ratio. The method of mixing the alloy powder and the dispersion medium is not particularly limited. The alloy powder and the dispersion medium may be prepared separately, and then the alloy powder and the dispersion medium may be weighed and mixed in a predetermined amount. In addition, when obtaining the alloy powder by dry-pulverizing the coarsely pulverized powder with a jet mill or the like, a collection container containing the dispersion medium may be placed at the alloy powder outlet of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization may be directly collected in the dispersion medium in the collection container to obtain a slurry. In this case, it is preferable that the atmosphere inside the collection container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly collected in the dispersion medium without being exposed to the air to obtain a slurry. Furthermore, it is also possible to wet-pulverize the coarsely pulverized powder in the dispersion medium using a vibration mill, ball mill, attritor, or the like to obtain a slurry consisting of the alloy powder and the dispersion medium.
[0053] The slurry thus obtained is molded in a known wet press to obtain a molded body having a desired size and shape, which is then sintered to obtain a sintered body.
[0054] <Step of Producing Sintered Rare Earth Magnet Material (S20)> Next, the powder compact is sintered to obtain a rare earth sintered magnet body (sintered body).
[0055] The powder compact is preferably sintered at a temperature in the range of 1000°C to 1150°C. To prevent oxidation due to sintering, residual gas in the atmosphere may be replaced with an inert gas such as helium or argon. The resulting sintered compact is preferably subjected to a heat treatment. The magnetic properties can be improved by the heat treatment. Known conditions for the heat treatment, such as the heat treatment temperature and time, can be adopted. The rare earth sintered magnet body thus obtained is subjected to a grinding / polishing process, a surface treatment process, and a magnetization process as necessary to complete the final rare earth sintered magnet.
[0056] <Step of Preparing Diffusion Source Powder (S22)> In the RMA alloy, which is a diffusion source, R includes at least one rare earth element and at least one of Nd and Pr. M is at least one selected from the group consisting of Cu, Ga, Co, and Fe. A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B.
[0057] The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire RMA alloy, the composition ratio of M is 5% by mass or more and 35% by mass or less of the entire RMA alloy, and the composition ratio of A is 0% by mass or more and 3% by mass or less of the entire RMA alloy.
[0058] The diffusion source can be prepared by a method for preparing a raw material alloy that is employed in a general manufacturing method typified by Nd-Fe-B sintered magnets, such as a die casting method, a strip casting method, a single roll super-quenching method (melt spinning method), or an atomizing method. The diffusion source may also be an alloy obtained by the above method, which has been pulverized by a known pulverizing means such as a pin mill. In order to improve the pulverizability of the alloy obtained by the above method, the alloy may be subjected to a heat treatment at 700°C or less in a hydrogen atmosphere to incorporate hydrogen, and then pulverized.
[0059] <Diffusion step of elements contained in diffusion source powder (S24)> By performing heat treatment at a temperature of 700°C or higher and 1100°C or lower in a vacuum or inert gas atmosphere, the elements contained in the diffusion source are diffused from the surface of the sintered body to the inside. In the present disclosure, this heat treatment is referred to as the first heat treatment. If the heat treatment temperature for diffusion is less than 700°C, the diffusion is insufficient and a high H cJ On the other hand, if the temperature exceeds 1100℃, abnormal grain growth of the main phase occurs, and H cJ The heat treatment temperature for diffusion is preferably 800°C or higher and 1000°C or lower. cJThe heat treatment time is set to an appropriate value depending on the composition and dimensions of the sintered body material and the diffusion source, the heat treatment temperature, etc., but is preferably 5 minutes to 30 hours, more preferably 10 minutes to 25 hours, and even more preferably 30 minutes to 20 hours. It is also preferable to prepare the diffusion source in an amount of 1 mass% to 30 mass% of the weight of the sintered body material. If the diffusion source is less than 1 mass% of the weight of the sintered body material, H cJ On the other hand, if it exceeds 30 mass%, B r may decrease.
[0060] The heat treatment for diffusion can be performed using a known heat treatment method. For example, the surface of the sintered body material can be covered with a powder layer of the diffusion source, and the first heat treatment can be performed. For example, the diffusion source can be coated on the surface of the sintered body material by a sputtering method, and then the first heat treatment can be performed. For example, a slurry in which the diffusion source is dispersed in a dispersion medium can be applied to the surface of the sintered body material, and the dispersion medium can be evaporated to bring the diffusion source into contact with the sintered body material. Examples of the dispersion medium include alcohol (ethanol, etc.), NMP (N-methylpyrrolidone), aldehydes, and ketones. In addition, the sintered body material that has been subjected to the first heat treatment can be subjected to known mechanical processing such as cutting or machining.
[0061] The sintered body material that has been subjected to the heat treatment for diffusion may be subjected to a heat treatment at a temperature of 450° C. or more and 600° C. or less in a vacuum or in an inert gas atmosphere. In the present disclosure, this heat treatment is referred to as a second heat treatment. By performing the second heat treatment, a high B r and high H cJ By setting the temperature of the second heat treatment to 450° C. or more and 600° C. or less, R6T 13 The formation of the Ga phase progresses. The second heat treatment temperature is preferably 480°C or higher and 560°C or lower. cJ The heat treatment time is set to an appropriate value depending on the composition and dimensions of the sintered body material, the heat treatment temperature, etc., and is preferably from 5 minutes to 20 hours, more preferably from 10 minutes to 15 hours, and even more preferably from 30 minutes to 10 hours.
[0062] According to this embodiment, the finely pulverized powder, which is in an active state immediately after being produced by the jet mill pulverizer and is therefore most susceptible to oxidation, can be prevented from being oxidized by the moisture dissolved in the oil in the collection container, resulting in a rare earth sintered magnet with modified two-particle grain boundaries. EXAMPLES
[0063] The present disclosure will be described in more detail below with reference to experimental examples, but the present disclosure is not limited thereto.
[0064] Experimental Example 1 A rare earth-based raw alloy (alloy for RTB-based sintered magnets) shown in Sample No. 1 in Table 1 was prepared. Specifically, an alloy of each element was prepared so as to have the composition shown in Sample No. 1 in Table 1, and an alloy for RTB-based sintered magnets was prepared by strip casting. The obtained alloy for RTB-based sintered magnets was coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powder. The coarsely pulverized powder was fed into a jet mill pulverizer 300 shown in FIG. 3, and pulverized to obtain fine powder. The average particle size (d50) of the obtained fine powder was 3.0 μm. The average particle size (d50) was measured using a particle size distribution analyzer "HELOS&RODOS" manufactured by Sympatec under the following conditions: dispersion pressure: 4 bar, measurement range: R2, calculation mode: HRLD.
[0065] The obtained fine powder was collected in the collection container 400 storing the oil previously supplied from the tank of the oil supply device 500 in FIG. 3. The moisture ratio, which is the ratio of the moisture mass in the oil to the mass of the powder to be collected, in the oil supplied to the collection container was adjusted as shown in Table 2. The moisture ratio was measured using a moisture meter in oil, TEKHNE Port-Oil, manufactured by Techne Measurement Co., Ltd. Thereafter, the fine powder was kept in the collection container 400 for 60 minutes, and then the fine powder was immersed in mineral oil in a nitrogen atmosphere to prepare a slurry. The slurry concentration was 75% by mass. The obtained slurry was molded (wet molding) in a magnetic field to obtain a molded body. The molding device used was a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.
[0066] The obtained compact was sintered in a vacuum at 1050°C (a temperature at which densification by sintering is sufficiently achieved) for 4 hours to obtain a sintered body. The density of the sintered body was 7.5 Mg / m3 or more. The sintered body was further subjected to a heat treatment in which it was held at 800°C for 2 hours, cooled to room temperature, and then held at 500°C for 2 hours, and cooled to room temperature to obtain RTB sintered magnets (Nos. 1 to 5). The O (oxygen content) of the obtained sintered magnets was measured using a gas fusion-infrared absorption method. The results are shown in Table 2. In addition, without storing the fine powder in the recovery container 400 for 60 minutes, the fine powder collected in the recovery container 400 was immediately immersed in mineral oil in a nitrogen atmosphere to prepare a slurry, and an RTB sintered magnet (No. A) was produced in the same manner as Nos. 1 to 5. The oxygen content of the produced magnet was measured and found to be 0.095% by mass. Table 2 shows the difference in oxygen content (Δoxygen content) between RTB based sintered magnet No. A and RTB based sintered magnets Nos. 1 to 5.
[0067] [Table 1]
[0068] [Table 2]
[0069] As shown in Table 2, the inventive examples (Nos. 1, 4, and 5) had lower oxygen contents than the comparative examples (Nos. 2 and 3), and the Δoxygen contents were also controlled to 400 ppm or less.
[0070] As described above, the present disclosure includes the methods for producing sintered rare earth magnets described in the following items. [Item 1] pulverizing a rare earth-based raw alloy to produce a powder of the rare earth-based raw alloy; recovering the powder using a recovery container; supplying an oil agent to the collection vessel before, after, or during the collection of the powder; adjusting the moisture ratio, which is the ratio of the moisture mass in the oil to the mass of the powder to be collected, in the oil solution supplied to the collection container to 0.005% or less; The method for producing a rare earth sintered magnet includes the steps of: [Item 2] 2. The method for producing a rare earth sintered magnet according to item 1, wherein the step of adjusting the moisture ratio to 0.005% or less comprises a step of passing an inert gas through the oil agent to reduce the moisture mass in the oil agent. [Item 3] The step of preparing the powder includes a step of pulverizing the rare earth-based raw alloy by a jet mill pulverizing device, Furthermore, supplying an inert gas to an inside of a pipe connecting the jet mill pulverizer to the recovery container and to a gas inlet pipe communicating with the inside of the recovery container; transferring the powder from the jet mill grinding device through the pipe filled with the inert gas to the collection vessel filled with the inert gas and the oil; Including, 3. The method for producing a rare earth sintered magnet according to item 2, wherein the dew point inside the piping and the recovery vessel is maintained at −80° C. or higher and −30° C. or lower. [Item 4] 4. The method for producing a rare earth sintered magnet according to item 3, wherein the gas inlet pipe is made of a fluororesin. [Item 5] 5. The method for producing a rare earth sintered magnet according to item 4, wherein a cyclone classifier is provided downstream of the jet mill pulverizer, and the piping connects the cyclone classifier and the recovery container. [Item 6] The composition of the rare earth-based raw alloy is R: 26.5 to 33.5 mass% (R is a rare earth element and must contain at least one of Nd and Pr), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85~0.92% by mass, T: 61.5 mass% or more (T is Fe and Co, and 90% or more of T is Fe by mass ratio), Tb: 0.30% by mass or less, and Dy: 0.30% by mass or less 6. The method for producing a rare earth sintered magnet according to any one of items 1 to 5, [Item 7] producing a powder compact from the powder collected in the collection container; a step of sintering the powder compact to produce a rare earth sintered magnet material; providing a diffusion source powder formed from an RMA alloy; a step of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material, thereby diffusing elements contained in the diffusion source powder into the inside of the rare earth sintered magnet material; Further comprising: In the RMA alloy, R contains at least one rare earth element and at least one of Nd and Pr; M is at least one selected from the group consisting of Cu, Ga, Co, and Fe; A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B; The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire RMA alloy. The composition ratio of M is 5% by mass or more and 35% by mass or less of the entire RMA alloy. 7. The method for producing a rare earth sintered magnet according to item 6, wherein the composition ratio of A is from 0 to 3 mass % of the entire RMA alloy. [Explanation of symbols]
[0071] 12 Main phase 14 Grain boundary phase 14a Two-grain grain boundary phase 14b Grain boundary triple point 100 Jet mill grinding device 200 Cyclone collector 300 Bag filter device 400 Collection container 500 Oil supply device
Claims
1. pulverizing a rare earth-based raw alloy to produce a powder of the rare earth-based raw alloy; recovering the powder using a recovery container; supplying an oil agent to the collection container before, after, or during the collection of the powder; adjusting the moisture ratio, which is the ratio of the moisture mass in the oil to the mass of the powder to be collected, in the oil solution supplied to the collection container to 0.005% or less; The method for producing a rare earth sintered magnet includes the steps of:
2. 2. The method for producing a rare earth sintered magnet according to claim 1, wherein the step of adjusting the moisture ratio to 0.005% or less includes a step of passing an inert gas through the oil to reduce the moisture mass in the oil.
3. The step of preparing the powder includes a step of pulverizing the rare earth-based raw alloy by a jet mill pulverizing device, Furthermore, supplying an inert gas to an inside of a pipe connecting the jet mill pulverizer to the recovery container and to a gas inlet pipe communicating with the inside of the recovery container; transferring the powder from the jet mill grinding device through the pipe filled with the inert gas to the collection vessel filled with the inert gas and the oil; Including, 3. The method for producing a rare earth sintered magnet according to claim 2, wherein the dew points inside said piping and said recovery vessel are maintained at -80° C. dp or higher and -30° C. dp or lower.
4. The method for producing a rare earth sintered magnet according to claim 3 , wherein the gas inlet pipe is made of a fluororesin.
5. 5. The method for producing a rare earth sintered magnet according to claim 4, wherein a cyclone classifier is provided downstream of said jet mill pulverizer, and said piping connects said cyclone classifier and said recovery container.
6. The composition of the rare earth-based raw alloy is R: 26.5 to 33.5 mass% (R is a rare earth element and must contain at least one of Nd and Pr), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85 to 0.92% by mass, T: 61.5 mass% or more (T is Fe and Co, and 90% or more of T is Fe by mass ratio); Tb: 0.30% by mass or less, and Dy: 0.30% by mass or less The method for producing a rare earth sintered magnet according to claim 1 ,
7. producing a powder compact from the powder collected in the collection container; a step of sintering the powder compact to produce a rare earth sintered magnet material; providing a diffusion source powder formed from an R-M-A alloy; a step of performing a heat treatment with the diffusion source powder attached to the surface of the rare earth sintered magnet material, thereby diffusing elements contained in the diffusion source powder into the inside of the rare earth sintered magnet material; Further comprising: In the R-M-A alloy, R is at least one rare earth element, including at least one of Nd and Pr; M is at least one selected from the group consisting of Cu, Ga, Co, and Fe; A is at least one selected from the group consisting of Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag, and B; The composition ratio of R is 65% by mass or more and 95% by mass or less of the entire R-M-A alloy, The composition ratio of M is 5% by mass or more and 35% by mass or less of the entire R-M-A alloy, 7. The method for producing a rare earth sintered magnet according to claim 6, wherein the composition ratio of A is from 0% to 3% by mass of the entire RMA alloy.
Citation Information
Patent Citations
Alloy for r-t-b-based rare earth sintered magnet, process for producing alloy for r-t-b-based rare earth sintered magnet, alloy material for r-t-b-based rare earth sintered magnet, r-t-b-based rare earth sintered magnet, process for producing r-t-b-based rare earth sintered magnet, and motor
WO2013008756A1
Cited By
Method for producing cation-modified silica and cation-modified silica dispersion
CN122831352A